“Sou mais cigano que morador”: relações interétnicas e a questão da identidade cigana em São João do Paraíso (MA) - CAVALCANTE , Janeide da Silva (2021)
This research aims to understand the Gypsy presence in São João do Paraíso (MA), seeking to identify, in the social relations established between Gypsies and the local po pulation, the process of their fixation in the city and how stereotypes and prejudices as sociated with Roma. We recognize the social interactions of Gypsies in the city, as well as throughout Brazil, being marked by a stigma (GOFFMAN, 2004) against this ethnic group, represented by stereotypes active/aged by non-Gypsies. I also consider the issue of identity, highlighting which categories are used to recognize their gypsyism. This work seeks to understand the Roma presence in the city in the face of the development of fri endly relations with the local population, in a positive moral perspective and observe how, in the articulation of identity, the Calon Roma, even as residents, define themselves as “ more gypsy than resident”. The methodology used for the research carried out with gypsies in São João do Paraíso includes direct observation and the use of informal con versations (WHYTE, 2005) (ROCHA; ERCKET, 2008), in addition to the use of questi onnaires applied by digital means with the non Gypsies residing in the municipality. This in-depth investigation identified how the beginning of relations between Roma and resi dents – marked by prejudice and activation of stereotypes – allow Roma to build negoti ation strategies and redirect stigma towards other Roma, thus seeking a positive represen tation in the city and building friendly relationships with residents. It was also identified how work was considered by them as a contributing factor in this negotiation in favor of a more positive image in the city, although incipient. Another characteristic evidenced in the relations between residents and Gypsies are compadrio ties and marriages between these ethnic groups. Furthermore, it was possible to observe how gypsies build their own ways of appropriating space, based on a Calon ethos, adding values to elements such as walking as an inherent mark of “being a gypsy”, thus emphasizing the ethnic belonging of being “ more gypsies than residents” among the Calons of São João Paraíso.